The flow over a rotating disc-wing - Potts, J. R.; Crowther, W. J. (Royal Aeronautical Society research forum, London, January 2000, 2000)
An experimental investigation into the aerodynamics of a rotating disc-wing has been carried out in an open-circuit wind tunnel, over a range of Reynolds number from 1.04×105 to 3.78×105. The disc-wing considered has an axisymmetric, approximately elliptic cross-section and hollowed out underside cavity. The spin rate was found to have only a small effect on the aerodynamic loads but shows some decrease in rolling moment. The lift and drag coefficients have been found to be independent of Reynolds number for the range of tunnel speeds tested. Observations from fluorescent paint (flow visualisation) patterns have revealed the surface flow regime. The upper surface flow is characterised by separation at a line (arc) of constant radius on the leading edge rim, followed by reattachment at a line of similar geometry. Trailing vortices detach from the trailing edge rim. The cavity flow is characterised by separation at the leading edge lip, followed by straight-line reattachment.